Scalable and Accurate Clones Detection Based on Metrics for Dependence Graph - Sevak S. Sargsyan; Shamil F. Kurmangaleev; Artiom V. Baloian; Hayk K. Aslanyan (Изд-во НАН РА)
The article describes a new method of code clones detection for C/C++ programming languages. The method is based on metrics for program dependence graph. For every node of program dependence graph a characteristic vector is constructed, which contains information about neighbors.
Keywords: Mathematics; Computer software; Graph theory